Humans-with-Media: Twenty-Five Years of a Theoretical Construct in Mathematics Education - Borba, Marcelo C. [UNESP]; Souto, Daise Lago P.; Cunha, José Fernandes T.; Domingues, Nilton S. [UNESP] (Springer Nature, 2024)
In this chapter, we discuss the genesis, the epistemological vision, and how the humans-with-media construct has been developed in dialog with activity theory, social semiotics, and other theories. We show how the construct has been transformed by different studies and its relation to different media. We also present research that relied on this theoretical construct to understand how digital technologies cause modifications in the production of mathematical knowledge. We address theorizations and situate the notion of the agency of media within the humans-with-media construct. We discuss how the power of the virus transformed classrooms – and society in general – during the pandemic period, as well as the challenges of doing education during and after the COVID-19 pandemic. It is emphasized how this construct may be helpful in the struggle for social justice within and beyond mathematics education.
Keywords: Activity theory; Agency of media; Digital technologies; Humans-with-media; Social inequality